Cardiac imaging in congenital heart disease during the coronavirus disease-2019 pandemic: recommendations from the Working Group on Congenital Heart Disease of the Italian Society of Cardiology - Sirico, Domenico (J Cardiovasc Med (Hagerstown), 2020)
The recent outbreak of 2019 severe acute respiratory syndrome coronavirus-2 is having major repercussions on healthcare services provision in Italy and worldwide. Data suggest the virus has a strong impact on the cardiovascular system, and cardiac imaging will play an important role in patients affected by coronavirus disease-2019. Although paediatric patients are mildly affected, they represent a clear accelerator in spreading the virus, and healthcare workers are at higher risk of infection. The aim of this position paper is to provide clinical recommendation regarding the execution of imaging investigations for the cardiac diagnostic work-up of paediatric patients with suspected or confirmed infection.